Stock Market Development and Financial Structure of Non- Financial Firms - AHMED, ZEESHAN; NASIR, MISHAL; ULLAH, WASEEM (The journal of contemporary issues in business and government, 2021)
The study seeks to investigate the relationship of stock market developent with financial structure of firms in Pakistan. Quantitative approach is used in this study. For this purpose, secondary data is obtained from published annual reports of 100 non-financial firms listed in Pakistan Stock Exchange from 2008-2018. The data related to stock index is obtained from daily KSE 100 stock index ranging from 2008 to 2018. Dynamic panel model has been used; two step system GMM panel estimators are applied for empirical testing of hypothesis. The study indicates that two stock market development measures like stock market capitalization and trading volume increases the debt level in financial structure. However, stock market volatility decreases the optimal financial structure of firms. The study is beneficial for corporate managers for efficient and optimal financial decision making. Moreover, the study has novel contribution in the relationship of various stock market development measures with number of financial structure measures.